Bad moms [videorecording (Blu-Ray + DVD) - Lucas, Jon, 1976-; Moore, Scott (Screenwriter); Kunis, Mila, 1983-; Bell, Kristen, 1980-; Hahn, Kathryn, 1974-; Hernandez, Jay, 1978-; Smith, Jada Pinkett, 1971-; Applegate, Christina, 1971-; Lennertz, Christopher; Denault, Jim, 1960-; Caston, Julia (Universal Pictures Home Entertainment, 2016)
When three overworked and under appreciated moms are pushed beyond their limits, they ditch their conventional responsibilities for a jolt of long overdue freedom, fun, and comedic self indulgence.